Free trade, mercantilism, and manufacturing: economic and business consequences of import tariffs - Strain, Michael (Henry Stewart Talks, 2025)
Tariffs, Trump administration, Free trade, US economic policy, Trade barriers, US manufacturing, Retraining workers, Community colleges, Trade policy, Geopolitics